2017
DOI: 10.1002/ags3.12023
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study on early start of chemotherapy after excising primary colorectal cancer with distant metastases (Pearl Star 02)

Abstract: Initiating chemotherapy usually requires a delay of more than 4 weeks after surgically resecting colorectal cancer. However, there is little evidence regarding the required delay interval. We have previously reported a pilot study to determine the safety and feasibility of early initiation of chemotherapy after resecting primary colorectal cancer with distant metastases. We aimed to determine the safety and efficacy of early initiation of chemotherapy after resecting colorectal cancer with distant metastases.T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Time to adjuvant therapy is a potential mid-term outcome measure that could be used to determine patient's overall recovery and performance [24], as it has been shown that delayed commencement of adjuvant chemotherapy (especially > 8 week) is linked to a worse overall survival in patients with CRC. One possible explanation of this is that early initiation of postoperative chemotherapy may prevent tumor growth or recurrence [25]. Since postoperative complications are one of the major reasons for delayed adjuvant chemotherapy [26], the benefits of ERAS, therefore, may go beyond just the immediate postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Time to adjuvant therapy is a potential mid-term outcome measure that could be used to determine patient's overall recovery and performance [24], as it has been shown that delayed commencement of adjuvant chemotherapy (especially > 8 week) is linked to a worse overall survival in patients with CRC. One possible explanation of this is that early initiation of postoperative chemotherapy may prevent tumor growth or recurrence [25]. Since postoperative complications are one of the major reasons for delayed adjuvant chemotherapy [26], the benefits of ERAS, therefore, may go beyond just the immediate postoperative period.…”
Section: Discussionmentioning
confidence: 99%